1996
DOI: 10.1046/j.1423-0410.1996.7110048.x
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of Antibodies to Cromer Blood Group System Antigens during Mid Pregnancy

Abstract: The Cromer blood group system consists of 7 high incidence and 3 low incidence antigens that are carried on the complement regulatory glycoprotein called decay-accelerating factor (DAF; CD55). Despite laboratory results that would predict clinical significance, antibodies with specificities in the Cromer blood group system have not been reported to cause hemolytic disease of the newborn. It is possible that strong expression of DAF on the apical surface of antigen-positive fetally derived placental trophoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
0
7
2
Order By: Relevance
“…Le, Lu, to cause HDFN may be due to paucity of antigen sites on fetal red cells or absorption of antibodies by fetal antigen in the placenta. [16] When alloantibodies are detected in the antenatal antibody screening, the antibody must be identified, since the alloantibody specificity is a clue to its potential risk for hemolysis.…”
Section: Spectrum Of Hemolytic Disease Of Newbornmentioning
confidence: 99%
“…Le, Lu, to cause HDFN may be due to paucity of antigen sites on fetal red cells or absorption of antibodies by fetal antigen in the placenta. [16] When alloantibodies are detected in the antenatal antibody screening, the antibody must be identified, since the alloantibody specificity is a clue to its potential risk for hemolysis.…”
Section: Spectrum Of Hemolytic Disease Of Newbornmentioning
confidence: 99%
“…6 The decline in the titer was thought to result from absorption of the antibody by white cells or platelets or be due to neutralization by plasma of the fetus. Another case of anti-Cr a in a pregnant woman in which the titer of the anti-Cr a decreased was described by Dickson et al 5 Reid et al 8 described two patients with repeat pregnancies who had Cromer blood group system antibodies (anti-Cr a and anti-Dr a ) with titers of 128 or greater at the beginning of pregnancy. These antibodies became undetectable in the serum from the second trimester onward.…”
Section: Discussionmentioning
confidence: 96%
“…7 The placental trophoblasts possess the DAF polymorphism of the fetus, which is inherited from both parents and is most likely positive for the high-prevalence Cromer antigens, including Dr a . Reid et al 8 suggested that antigen-positive trophoblasts may absorb maternal antibodies with DAF specificity such as anti-Dr a , causing their disappearance from maternal blood and explaining the lack of HDN secondary to this antibody. They reported two cases with Cromer antibodies, one of them anti-Dr a , which disappeared during pregnancy, supporting their hypothesis.…”
mentioning
confidence: 99%
“…The DAT performed on the cord RBCs of five of these babies was negative (in the lone anti-CRAM case the neonatal DAT was not reported 19 ), and there was no evidence of HDFN in any of these cases. 25,71,72 In three of the cases the antibody, including anti-CRAM, was detected again in the serum of these women after delivery, again suggesting an adsorption mechanism rather than the cessation of antibody production. 19,71 Although no cases of fetal demise have been directly attributed to Cromer antibodies, it is worthwhile to point out that in at least one case, anti-Cr a was detectable at a titer of 128 by week 15 and had declined to a titer of 8 by week 20, which was 2 weeks before fetal demise.…”
Section: Clinical Significance Of Cromer Antibodiesmentioning
confidence: 89%
“…25,71,72 In three of the cases the antibody, including anti-CRAM, was detected again in the serum of these women after delivery, again suggesting an adsorption mechanism rather than the cessation of antibody production. 19,71 Although no cases of fetal demise have been directly attributed to Cromer antibodies, it is worthwhile to point out that in at least one case, anti-Cr a was detectable at a titer of 128 by week 15 and had declined to a titer of 8 by week 20, which was 2 weeks before fetal demise. The role of the antibody in the demise is not known, and this patient's next pregnancy was successfully carried to term despite the presence of anti-Cra at a maximum titer of 64 at week 7.…”
Section: Clinical Significance Of Cromer Antibodiesmentioning
confidence: 89%